The Dilemma Between Translation and Adaptation - Aymerich-Lemos, Sílvia; Beaulieu, Hélène; Centelles, Josep Joan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
It is not always possible to convey the full meaning of a text while translating it. A novel aiming at transmitting knowledge to young readers will often contain information not useful to readers in another country, while new information may have to be added for these readers. The reflection on how to solve the difficulties encountered in translating four texts, the various translation typologies that were used and a generalization of when these typologies are the best solution bring to the translation – adaptation dilemma the observations made from translating novels with scientific content aimed at young readers.